Development of a Passive Vibration Damping Structure for Large Solar Arrays Using a Superelastic Shape Memory Alloy with Multi-Layered Viscous Lamination - Gi-Seong Woo; Jae-Hyeon Park; Sung-Woo Park; Hyun-Ung Oh (Aerospace)
In the space environment, the elastic vibrations of satellite solar panels are caused by various factors that disturb satellite missions. Therefore, we propose a multi-layered high-damping yoke structure based on a passive control method. To optimize the proposed yoke structure, we performed a free vibration test on various multi-layered blade specimens and designed a yoke structure with the maximum damping performance based on the test results. This high-damping yoke structure was mounted on a dummy solar panel with flexible mode (0.79 Hz) and basic characteristic tests were performed to validate the effectiveness of the solar panel vibration suppression. The test results demonstrated that the proposed multi-layered high-damping yoke is effective in suppressing the vibrations of the first and second modes. In addition, a thermal vacuum test was performed to investigate the delamination between multi-layered structures, and the test results proved the applicability of the proposed yoke structure in an actual space environment.